PERTUMBUHAN, SINTASAN DAN PRODUKSI IKAN NILA MERAH (Oreochromis niloticus) YANG DIBERI KOMBINASI PAKAN KOMERSIL DAN AMPAS TAHU HASIL FERMENTASI - Hidayat Suryanto Suwoyo; Sri Redjeki Hesti Mulyaningrum; Rachman Syah (BERITA BIOLOGI, 2018)
The study aimed to evaluate the combination between commercial feed and fermented tofu waste feeding for growth, survival rate and production of red Tilapia Oreochromis niloticus in pond. The study was conducted in Experimental Pond Installation of Research Institute for Coastal Aquaculture, Maros, South Sulawesi, using eight ponds with 2,500 m2 in size. Red Tilapia fingerlings (±8 cm in length) were reared for 112 days with 1 individu/m2 of stocking density. The feeding treatments were of 100% commercial feed (A), 75% commercial feed + 25% fermented tofu waste (B), 50% commercial feed + 50% fermented tofu waste (C), and 25% commercial feed + 75% fermented tofu waste (D). Feeding frequency was given twice a day using concentration 10% of biomass weight in the first month, and decreased by 3% of biomass weight in the fourth month. Experimental was designed by a completely randomized designed consisted of four treatments and two replications for each treatment. Observed variables were growth, survival rate, feed conversion ratio, production, and water quality. Present study indicated that different levels of combination of commercial feed and fermented tofu waste had significant effect on growth (P<0.05), but did not have significant effect on survival rate, production, and feed conversion ratio (P>0.05). Feeding by combination of 75% commercial feed + 25% fermented tofu waste could be utilized optimally by Tilapia. During experiment, pond water quality was in conducive condition to support the growth and survival rate of red Tilapia.